1998
DOI: 10.1046/j.1460-9568.1998.t01-1-00285.x
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA-induced dyskinesia in the rat is associated with striatal overexpression of prodynorphin- and glutamic acid decarboxylase mRNA

Abstract: Rats sustaining unilateral near-complete 6-hydroxydopamine lesions of the mesostriatal dopamine pathway received daily injections of 3, 4 dihydroxyphenyl-l-alanine (L-DOPA, 8 mg/kg plus 15 mg/kg benserazide) for 3 weeks. During this period, about 50% of the rats gradually developed abnormal involuntary movements, lasting for 2-3 h following each L-DOPA dose. Rats were killed 3 days after the last L-DOPA injection, and sections through the striatum were processed for in situ hybridization histochemistry. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
272
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(295 citation statements)
references
References 64 publications
18
272
1
4
Order By: Relevance
“…Higher doses of L-DOPA of 25 and 50 mg/kg, however, produced stereotypic movements and enhanced locomotor activity that interfered with the execution of the RT task. These movements were the expression of enhanced manifestations of normal rodent behavior (grooming, sniffing and rearing) rather than abnormal involuntary movements as previously observed after chronic L-DOPA treatment (Cenci et al 1998;Henry et al 1998;Lundblad et al 2002;Mura et al 2002). The lack of dyskinesia in our experimental conditions after long-term L-DOPA administration is probably related to the partial DA depletion of the striatum (40-50% denervation) produced by the local infusion of 6-OHDA in the striatum.…”
Section: Functional Interactions Between Mglur5 and L-dopasupporting
confidence: 73%
“…Higher doses of L-DOPA of 25 and 50 mg/kg, however, produced stereotypic movements and enhanced locomotor activity that interfered with the execution of the RT task. These movements were the expression of enhanced manifestations of normal rodent behavior (grooming, sniffing and rearing) rather than abnormal involuntary movements as previously observed after chronic L-DOPA treatment (Cenci et al 1998;Henry et al 1998;Lundblad et al 2002;Mura et al 2002). The lack of dyskinesia in our experimental conditions after long-term L-DOPA administration is probably related to the partial DA depletion of the striatum (40-50% denervation) produced by the local infusion of 6-OHDA in the striatum.…”
Section: Functional Interactions Between Mglur5 and L-dopasupporting
confidence: 73%
“…Unilaterally 6-OHDA lesioned rats receiving a low dose of levodopa gradually developed AIMs affecting the side of the body contralateral to the lesion as previously described (Cenci et al 1998;Marin et al 2006a). The movements were present during approximately 2 h after levodopa administration, and their evolution is similar to the time course of peak-dose dyskinesia that occurs in PD.…”
Section: Discussionmentioning
confidence: 69%
“…The AIMs observed in the present study were gradually induced by levodopa treatment, affected cranial, trunk and limb musculature, and were restricted the side of the body contralateral to the lesion. Thus, AIMs in this model may be considered as similar to levodopa-induced dyskinesia in parkinsonian patients (Cenci et al 1998;Marin et al 2006a;Winkler et al 2002). We found that systemic administration of the mGluR5 glutamate antagonist MPEP reduced the intensity of dyskinetic movements elicited by chronic administration of levodopa.…”
Section: Discussionmentioning
confidence: 71%
“…Many of the models employed use rodent species and have proved helpful in evaluating the antiparkinsonian activity of drugs (Cenci et al 1998;Lundblad et al 2002;Papa et al 1994). However, the use of non-human primate models of the disorder, in which pathobiological changes are more homologous and changes in motor behavior more closely resemble those that occur in humans, has already proved extremely valuable in evaluating factors responsible for the onset and maintenance of motor abnormalities in clinical Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%